A Multitarget Approach toward the Development of 8‐Substituted Purines for Photoprotection and Prevention of UV‐Related Damage. (3rd May 2017) - Djuidje, Ernestine N.; Dissette, Valeria; Bino, Alessia; Benetti, Simonetta; Balzarini, Jan; Liekens, Sandra; Manfredini, Stefano; Vertuani, Silvia; Baldisserotto, Anna
Abstract: Ultraviolet (UV) light is the most abundant and significant modifiable risk factor for skin cancer and many other skin diseases such as early photo‐aging. Across the solar radiation spectrum, UV light is the main cause behind skin problems. In the search for novel photoprotective compounds, a new series of 8‐substituted purines were synthesized from commercially available 6‐hydroxy‐4, 5‐diaminopyrimidine hemisulfate or 4, 5‐diaminopyrimidine. All title compounds were investigated for their UV filtering, antioxidant, antifungal, and antiproliferative activities. For the photoprotection assays we used a diffuse transmittance technique to determine the sun protection factor (SPF) in vitro, and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) and ferric ion reducing antioxidant power (FRAP) tests for evaluating the antioxidant activity of the more potent compounds. Among them, 8‐(2, 5‐dihydroxyphenyl)‐7 H ‐purin‐6‐ol (compound26 ) proved to be a good radical scavenger and is also endowed with broad‐spectrum UVA filtering capabilities, suitable for further development as a protective molecule. Abstract : Multitasking purines ! A series of 8‐substituted purines was synthesized and evaluated for antioxidant, UV‐filtering, antifungal, and antiproliferative activities. We discovered compounds with high antioxidant activity, capacity as potential broad‐spectrum UVA filters, and good inhibitory activity toward human endothelial HMEC‐1 cells. The best multifunctional compound has hydroxy groups at positions 2 and 5 of the phenyl ring and at position 6 of the purine ring.